ENTREPRENEURSHIP TRAINING ON THE PERFORMANCE OF MICRO, SMALL, AND MEDIUM ENTERPRISES IN AMBON CITY - Albertus Lalaun; Victor Cornelis (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
Training, coaching, and businessmen skills are factors that influence how well SMEs function. This study intends to determine whether businessman training, coaching, and skill models have an impact on MSME actors' performance. In this study, the population consists of MSMEs who have participated in training and coaching provided by service cooperatives and small and medium-sized businesses, with a sample size of 71 respondents. In this study, survey methods were used to collect data, and partial least squares was used as a tool for data analysis. According to the study's findings, training, coaching, and entrepreneurial abilities all have a big impact on how well MSME actors perform; the greater the training and coaching, the better the performance of the perpetrator MSMEs.